LEGAL ANALYSIS OF THE ENFORCEMENT OF DEFAULT JUDGMENTS IN THE RESOLUTION OF DEBT DISPUTES: ANALISIS HUKUM PELAKSANAAN PUTUSAN VERSTEK DALAM PENYELESAIAN SENGKETA HUTANG PIUTANG - Heristiawan Aryo Wirotomo; Agus Pramono (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2026)
This study examines the implementation of default judgments (verstek) in the settlement of debt disputes through a normative legal approach. A default judgment, rendered when the defendant fails to appear without a valid reason, is intended to ensure legal certainty and efficiency in resolving civil cases. However, in practice, it often raises issues of substantive justice, particularly concerning the validity of the defendant’s summons, the adequacy of evidence, and the protection of the defendant’s right to file an objection (verzet). By analyzing the provisions of the Herzien Indonesisch Reglement (HIR), Reglement Buitengewesten (RBg), and developments in judicial practice, this study reveals tensions between the principles of legal certainty, justice, and a fast and low-cost trial. Normatively, default judgments provide certainty and efficiency, as they allow judges to resolve disputes despite the defendant’s absence. Nevertheless, from the perspective of justice, weaknesses in the summons mechanism, limited verification of evidence, and execution carried out without the defendant’s involvement may disadvantage the weaker party. This study also highlights the need for reform in the regulation of default judgments to make them more adaptive to modern legal developments, including digitalized summons, stricter evidentiary standards, and broader access to verzet mechanisms. The findings suggest that the implementation of default judgments in debt disputes requires reformulation to not only uphold legal certainty and efficiency but also to prioritize the protection of parties’ rights. Thus, default judgments can serve as instruments of dispute resolution that are both effective and just